Morfología cráneoâˆ’mandibular del oso andino Tremarctos ornatus (Carnivora: Ursidae) - Stucchi, Marcelo; Figueroa, Judith (THERYA, 2013)
We described and illustrated the skull and jaw of the andean bear Tremarctos ornatus, comparatively analyzing among individuals of different ages and sexes, and adults of other species of Ursidae. In ontogenetic level, we found the following morphological changes associated with senescence: obliteration of the sutures, crests development, widening of the zygomatic arches and frontalized orbits, muzzle and occipital region elongation, and tooth wear. We also found that as the length between the front edge of the premolar 4 and the rear edge of molar 2 in the skull is the most stable. This allowed to calculate proportions showing that the width of the skull at the level of the zygomatic arches and postorbital processes, and the length of the braincase, no overlap between adults male and female, which would use them to differentiate sexes. According feeding habits, mostly herbivores, were recognized following craniomandibular characteristics: short skull, straight and well developed zygomatic arches, large areas for the insertion of the temporalis and masseter muscles in the mandibles with condyle located above the teeth level, tooth wear, and large and frontalization trend of the orbits. Keywords: andean bear, bones, craniomandibular morphology, Tremarctinae, Tremarctos ornatus, Ursidae.